Antimicrobial Terpenes Suppressed the Infection Process of Phytophthora in Fennel-Pepper Intercropping System - Yang, Yuxin; Li, Ying; Mei, Xinyue; Yang, Min; Huang, Huichuan; Du, Fei; Wu, Jiaqing; He, Yiyi; Sun, Junwei; Wang, Haining; He, Xiahong; Zhu, Shusheng; et al. (Frontiers in Plant Science, 2022)
The interactions between non-host roots and pathogens may be key to the inhibition of soilborne pathogens in intercropping systems. Fennel (Foeniculum vulgare) can be intercropped with a wide range of other plants to inhibit soilborne pathogens in biodiversity cultivation. However, the key compounds of fennel root exudates involved in the interactions between fennel roots and pathogens are still unknown. Here, a greenhouse experiment confirmed that intercropping with fennel suppressed pepper (Capsicum annuum) blight disease caused by Phytophthora capsici. Experimentally, the roots and root exudates of fennel can effectively interfere with the infection process of P. capsici at rhizosphere soil concentrations by attracting zoospores and inhibiting the motility of the zoospores and germination of the cystospores. Five terpene compounds (D-limonene, estragole, anethole, gamma-terpenes, and beta-myrcene) that were identified in the fennel rhizosphere soil and root exudates were found to interfere with P. capsica infection. D-limonene was associated with positive chemotaxis with zoospores, and a mixture of the five terpene compounds showed a strong synergistic effect on the infection process of P. capsici, especially for zoospore rupture. Furthermore, the five terpene compounds can induce the accumulation of reactive oxygen species (ROS), especially anethole, in hyphae. ROS accumulation may be one of the antimicrobial mechanisms of terpene compounds. Above all, we proposed that terpene compounds secreted from fennel root play a key role in Phytophthora disease suppression in this intercropping system.